One-Pot Reverse Transcriptional Loop-Mediated Isothermal Amplification (RT-LAMP) for Detecting MERS-CoV - Lee, Se Hee; Baek, Yun Hee; Kim, Yang-Hoon; Choi, Young-Ki; Song, Min-Suk; Ahn, Ji-Young (Frontiers in Microbiology, 2017)
Due to the limitation of rapid development of specific antiviral drug or vaccine for novel emerging viruses, an accurate and rapid diagnosis is a key to manage the virus spread. We developed an efficient and rapid method with high specificity for the Middle East Respiratory Syndrome coronavirus (MERS-CoV), based on one-pot reverse transcription loop-mediated isothermal amplification (one-pot RT-LAMP). A set of six LAMP primers (F3, B3, FIP, BIP, LF (Loop-F), and LB (Loop-B) were designed using the sequence of nucleocapsid (N) gene with optimized RT-LAMP enzyme conditions: 100 U M-MLV RTase and 4 U Bst polymerase, implying that the reaction was able to detect 4 infectious viral genome copies of MERS-CoV within a 60 min reaction time period. Significantly, EvaGreen dye has better signal read-out properties in one-pot RT-LAMP reaction and is more compatible with DNA polymerase than SYBR green I. Isothermally amplified specific N genes were further evaluated using field-deployable microchamber devices, leading to the specific identification of as few as 0.4 infectious viral genome copies, with no cross-reaction to the other acute respiratory disease viruses, including influenza type A (H1N1 and H3N2), type B, human coronavirus 229E, and human metapneumovirus. This sensitive, specific and feasible method provides a large-scale technical support in emergencies, and is also applied as a sample-to-detection module in Point of Care Testing (POCT) devices.